2021
DOI: 10.1097/md.0000000000026574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic signature of ovarian cancer based on 14 tumor microenvironment-related genes

Abstract: Background: Ovarian cancer is one of the lethal gynecological diseases in women. However, using tumor microenvironment related genes to identify prognostic signature of ovarian cancer has not been discussed in detail. Methods: The mRNA profiles of 386 ovarian cancer patients were retrieved from The Cancer Genome Atlas. Univariate Cox regression and LASSO Cox regression analyses were performed and 14 optimized prognostic genes related to tumor microenvironment were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In addition, Mirco Friedrich showed that memory CD8 T cells may pass through a certain signal transduction that drives the differentiation of immune B cells to CD4 T cells [ 32 ], which may explain the decrease of immune B cells and the increase of memory CD8 T cells in the high-risk group. Experiments by Daniele Fanale et al showed that the low expression of PD-1, PD-L1, BTN3A1, pan-BTN3As, BTN2A1, and BTLA can be used as markers for the diagnosis of advanced high-grade serous OV [ 33 ], and Xiazi Nie et al also proved that immune checkpoints, CTLA4, IDO1, and LAG3 are all associated with poor prognosis in OV [ 34 ], in addition, CXCL10 and CD27 infiltration is associated with anti-tumor immunity and treatment response in OV subtypes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mirco Friedrich showed that memory CD8 T cells may pass through a certain signal transduction that drives the differentiation of immune B cells to CD4 T cells [ 32 ], which may explain the decrease of immune B cells and the increase of memory CD8 T cells in the high-risk group. Experiments by Daniele Fanale et al showed that the low expression of PD-1, PD-L1, BTN3A1, pan-BTN3As, BTN2A1, and BTLA can be used as markers for the diagnosis of advanced high-grade serous OV [ 33 ], and Xiazi Nie et al also proved that immune checkpoints, CTLA4, IDO1, and LAG3 are all associated with poor prognosis in OV [ 34 ], in addition, CXCL10 and CD27 infiltration is associated with anti-tumor immunity and treatment response in OV subtypes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is difficult in the early stages of OV [30]. Among the gynecological malignancies, the high mortality rate associated with OV poses a severe threat to the lives of women [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mirco Friedrich showed that memory CD8 T cells may pass through A certain signal transduction that drives the differentiation of immune B cells to CD4 T cells [25], which may explain the decrease of immune B cells and the increase of memory CD8 T cells in the high-risk group. Experiments by Daniele Fanale et al showed that the low expression of PD-1, PD-L1, BTN3A1, pan-BTN3As, BTN2A1, and BTLA can be used as a marker for the diagnosis of advanced high-grade serous OV [26], and Xiazi Nie et al also proved that immunological examination Points CTLA4, IDO1, LAG3 are all associated with poor prognosis in OV [27], in addition, CXCL10, CD27 in ltration is associated with anti-tumor immunity and treatment response in OV subtypes [28,29].…”
Section: Discussionmentioning
confidence: 99%